(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The most prevalent and varied class of organic chemicals is comprised of heterocycliccompounds. Heterocyclic compounds have been produced in substantial quantities up to this time. Dueto significant synthetic study as well as their usefulness in other synthetic processes, heterocyclicmolecules are fast growing in number. In the realm of medicinal chemistry, these substances are used ina variety of applications. Additional well-known uses include dyestuff, cleansers, antifouling,antioxidants, and copolymer production. An effective method for generating newly discoveredheterocyclic compounds and their moieties always has distinctive qualities. Prior studies indicate thatmore than 90 of medications using heterocyclic compounds were created following the acquisition of asolid scientific understanding of the biological system. They have antiprotozoal, anthelminthic,antimalarial, antiviral, anti-inflammatory, antimicrobial, anti-mycobacterial, and ant parasitic properties.In this review, we cover the vast majority of bio - active heterocycles that have previously been preparedor drawn from flora, which include fungicidal,bactericidal, anti-oxidant, antidepressants, anti- allergic,anti-inflammatory, and anti - carcinogenic phytochemicals.